FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEIKUTSERTAAN IBU BALITA DALAM PEMBERIAN IMUNISASI BOOSTER DPT DAN CAMPAK DI POSYANDU BUKIT SERUNI WILAYAH KERJA PUSKESMAS LEPO-LEPO - Romantika, I Wayan; Wiwik Juni Suarnamib, Putu; Mien, Mien (JURNAL KEPERAWATAN, 2024)
Background: Immunisation is one of the government's steps in preventing certain diseases. After getting complete basic immunisation, it is still continued with booster immunisation to increase the immunity of toddlers. The success of the immunisation program is influenced by several factors such as education, parental employment, family support and the role of medical personnel. Objective: This study aims to determine the factors associated with the participation of mothers of toddlers in giving DPT and measles booster immunisation aged 18-24 months. Methode: The research design used in this study was cross sectional with a sample size of 47 respondents. Result: The results showed that there was no relationship between maternal age and maternal participation in DPT booster immunisation and measles aged 18-24 months (ρ value = 0.792), maternal knowledge (ρ value = 0.001) which means there is a relationship between knowledge and participation in booster immunisation and maternal employment (ρ value = 0.01), meaning there is a relationship between employment and participation in DPT booster immunisation and measles aged 18-24 months at BLUD UPTD Puskesmas Lepo-Lepo. Conclusion: The conclusion in this study is that employment status and knowledge are factors associated with maternal participation in booster immunisation. It is recommended that parties increase socialisation about the importance of DPT and measles booster immunisation Keywords: diphtheria; pertussis; tetanus; immunization; employment